Boosting chiral amplification in plasmon-coupled circular dichroism using discrete silver nanorods as amplifiers. Issue 60 (5th July 2021) - Wang, Wenhe; Wu, Fengxia; Zhang, Yanqun; Wei, Wenli; Niu, Wenxin; Xu, Guobao
Abstract : An unprecedented enhancement factor of over 3000 times is demonstrated in plasmon-coupled circular dichroism by using discrete Ag nanorods as amplifiers, providing an ultrasensitive platform for the chiral discrimination of cysteine. Abstract : Remarkable chiral amplification in plasmon-coupled circular dichroism spectroscopy (CD) is demonstrated by using discrete Ag nanorods as amplifiers. An unprecedented CD enhancement factor of over 3000 times is achieved without resonant or near-resonant exciton–plasmon couplings.